Giant coronary artery aneurysm with a thrombus secondary to Kawasaki disease - Patil Sushant; Shirodkar Salil; Pinto Robin; Dalvi Bharat (Wolters Kluwer Medknow Publications, 2008)
Although coronary artery aneurysms occur in Kawasaki disease, giant aneurysms are rare. We report a very large coronary artery aneurysm, measuring 25 mm and involving left anterior descending artery, in a 2-year-old child with Kawasaki disease. The challenges in management of such a patient have been highlighted.